2013
DOI: 10.1530/joe-12-0565
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin 1β in the anti-adipogenic action of macrophages on human preadipocytes

Abstract: When adipose tissue accumulates in obesity, the ability of preadipocytes to differentiate permits a hyperplastic expansion of functional adipocytes that preserves insulin sensitivity. Adipose infiltration by macrophages is associated with an adipogenic deficit and the appearance of inflamed, insulin-resistant hypertrophied adipocytes. Interleukin 1b (IL1b) has been reported to account for the anti-adipogenic action of macrophages in a mouse model. Using the THP-1 human macrophage cell line and human primary pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 36 publications
3
15
0
1
Order By: Relevance
“…Thus, as has been shown recently, insulin-dependent induction of CCL2 (MCP-1) could be an early step in the recruitment of additional inflammatory cells into the expanded adipose tissue (24). IL-1␤ released from macrophages has been envisaged as major factor causing insulin resistance in adipocytes (2) and is a strong inhibitor of adipocyte differentiation (8). An insulin-induced production of IL-1␤ might thus contribute to the unfavorable phenotype of adipose tissue with large lipid-overloaded and insulinresistant adipocytes found in obese patients.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, as has been shown recently, insulin-dependent induction of CCL2 (MCP-1) could be an early step in the recruitment of additional inflammatory cells into the expanded adipose tissue (24). IL-1␤ released from macrophages has been envisaged as major factor causing insulin resistance in adipocytes (2) and is a strong inhibitor of adipocyte differentiation (8). An insulin-induced production of IL-1␤ might thus contribute to the unfavorable phenotype of adipose tissue with large lipid-overloaded and insulinresistant adipocytes found in obese patients.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown that macrophage-conditioned medium inhibited adipogenesis in 3T3-L1 and human preadipocytes (11, 17). Moreover, IL-1β KO mice being high-fat fed (HFF) had lower mRNA levels of proinflammatory factors, increased expression of the adipogenic genes ( Pparγ, Cebpα, Cebpβ, Fabp4 ) in adipose tissue and less hepatic steatosis compared with wild-type HFF mice, which suggests that IL-1β could impair fat storage and promote ectopic fat accumulation by limiting adipose tissue expandability (37).…”
Section: Discussionmentioning
confidence: 91%
“…The mean age of the patients was 53 ± 9 years and the mean body mass index was 33 ± 10 ( ± SD). The stromal preadipocytes were isolated as previously described [18]. Connective tissue and capillaries were removed by dissection and tissue was digested with collagenase CLS type 1 (200 U/g of tissue; Worthington), followed by sequential size filtration through 200, 100, 50, and 25 μm filters.…”
Section: Human Subcutaneous Preadipocyte Isolation and Culturementioning
confidence: 99%